Comparative Study on Effects of Nebulized and Oral Salbutamol on a Cecal Ligation and Puncture-Induced Sepsis Model in Rats - Ozogul, B.; Halici, Z.; Cadirci, E.; Karagoz, E.; Bayraktutan, Z.; Yayla, M.; Akpinar, E.; Atamanalp, S. S.; Unal, D.; Karamese, M. (Drug Research, 2015)
Aim: The present study aimed to compare the effects of different routes of salbutamol administration (oral and nebulized) at different doses in a cecal ligation and puncture-induced (CLP-induced) sepsis model of rats.Methods: Rats were separated into 8 groups: 1) sham, 2) sham+4 mg/kg oral salbutamol, 3) sham+6 min 2 mg/ml nebulized salbutamol, 4) CLP, 5) CLP+2 mg/kg oral salbutamol, 6) CLP+4 mg/kg oral salbutamol, 7) CLP+3 min 2 mg/ml nebulized salbutamol, 8) CLP+6 min 2 mg/ml nebulized salbutamol. Subsequently, sepsis was induced by CLP through 16 h.Results: CLP-induced sepsis increased serum cytokine levels (TNF-α, IL-1β, and IL-6), increased tissue oxidative stress (8-Isoprosraglandin F2α), decreased antioxidant parameters (SOD, GSH), and increased lung injury by inflammatory cell accumulation.Conclusion: This study showed for the first time that oral administration of salbutamol exerted protective effects on CLP-induced sepsis and related lung injury in rats. We conclude that despite the greater side effects of oral salbutamol, it should be considered for administration in oral form due to its systemic effectiveness during septic conditions in emergency settings.
Keywords: salbutamol; β-adrenergic receptor; sepsis; cytokine; oxidative stress; rat